1991
DOI: 10.1021/bi00238a002
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the triosephosphate isomerase-phosphoglycolohydroxamate complex: an analog of the intermediate on the reaction pathway

Abstract: The glycolytic enzyme triosephosphate isomerase (TIM) catalyzes the interconversion of the three-carbon sugars dihydroxyacetone phosphate (DHAP) and D-glyceraldehyde 3-phosphate (GAP) at a rate limited by the diffusion of substrate to the enzyme. We have solved the three-dimensional structure of TIM complexed with a reactive intermediate analogue, phosphoglycolohydroxamate (PGH), at 1.9-A resolution and have refined the structure to an R-factor of 18%. Analysis of the refined structure reveals the geometry of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
233
3
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(252 citation statements)
references
References 22 publications
(32 reference statements)
14
233
3
2
Order By: Relevance
“…Crystal structures of TIM from chicken, yeast, and trypanosome, 1.8, 1.9, and 2.5 Å resolution, respectively, were solved in complex with PGH (46,57,58). The active sites of the three structures are identical; therefore, below we refer to only the yeast enzyme (Fig.…”
Section: Comparison Of Pgi͞5pah To Complexes Of Tim and Xyl With Analmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystal structures of TIM from chicken, yeast, and trypanosome, 1.8, 1.9, and 2.5 Å resolution, respectively, were solved in complex with PGH (46,57,58). The active sites of the three structures are identical; therefore, below we refer to only the yeast enzyme (Fig.…”
Section: Comparison Of Pgi͞5pah To Complexes Of Tim and Xyl With Analmentioning
confidence: 99%
“…This substitution of a nitrogen atom in place of C1 results in a planar hydroxamic acid moiety, possibly in the hydroximic or hydroximate form within the active site, in place of the cis-enediol(ate) at C1 and C2 and is stable enough in the conditions reported herein for structural studies of the enzyme͞inhibitor complex. Similar hydroxamic acid ligands have been used successfully in biochemical and structural studies of two other sugar isomerases, triosephosphate isomerase [TIM (46)] and xylose isomerase [XYL (47)]. A crystal structure of PGI with bound 5PAH would result in an improved model of how the cis-enediol(ate) intermediate binds in the active site and provide the most accurate distances between the reactive intermediate and catalytic amino acid residues.…”
mentioning
confidence: 99%
“…Alterations to the shape or charge of these amino acids should disrupt tertiary interactions. To test this prediction, the conserved residue positions in the aligned TIM genes were assigned to seven structural classes by examination of the yeast crystal structure (17). Because the (␤͞␣) 8 barrel is composed of a repeated structural motif, each structural class is represented by multiple residues.…”
Section: Mutability At Phylogenetically Hydrophobic and Polar Positionsmentioning
confidence: 99%
“…5). Structural studies revealed an ␣͞␤ fold, now known as the TIM-barrel (6)(7)(8), and elucidated the geometry of the catalytic residues at the active site and their interactions with the ligands (9).…”
mentioning
confidence: 99%